Select, Plan, Attend: How the Engagement of Cognitive Processes Influences Visuomotor Adaptation - Wijeyaratnam, Darrin (Université d'Ottawa | University of Ottawa, 2026)
Visuomotor adaptation has traditionally been viewed as an implicit (unconscious) process, driven by sensory prediction errors. However, growing evidence suggests that explicit (conscious strategy) processes, driven by target errors, also contribute to visuomotor adaptation. The overarching aim of this dissertation was to examine how the engagement of cognitive processes during training influence visuomotor adaptation and underlying explicit and implicit contributions. Across three experiments, participants performed reaches while the trajectory of cursor feedback was rotated 40° clockwise relative to their hand motion. Cognitive engagement was manipulated by requiring participants to (1) make a task-relevant choice (Select), (2) pre-plan a movement strategy (Plan), or (3) focus their attention (Attend). In Experiment 1 (Select), a choice group selected their reach target prior to moving, while a yoked group reached to targets in the same order as participants in the choice group. Choice increased perceived autonomy, yet it did not enhance overall visuomotor adaptation. Notably, the choice group demonstrated greater explicit adaptation and longer movement preparation times compared to the yoked group, suggesting increased strategic engagement without affecting implicit adaptation. In Experiment 2 (Plan), participants reported their intended movement strategy with respect to the direction their hand should aim (direction group), or where their hand should end (endpoint group) for the cursor to land on the target, while a control group reported no pre-planned movement strategy. Reporting a directional strategy resulted in a greater extent of early visuomotor adaptation compared to both the endpoint and control groups, and greater explicit adaptation compared to the control group. These findings highlight that the locus of one’s movement strategy impacts visuomotor adaptation and the engagement of underlying explicit processes. In Experiment 3 (Attend), participants adopted either an internal (hand) or external (cursor) focus of attention. The internal focus group demonstrated greater visuomotor adaptation than the external focus group during training, although explicit and implicit adaptation were comparable between groups. Together, our results reveal that visuomotor adaptation is not solely an implicit, error-driven process. Instead, visuomotor adaptation can be shaped by cognitive engagement during training. This work underscores the need for broader models of sensorimotor learning that integrate cognitive, strategic, and motivational influences.
Keywords: Motor learning; Visuomotor adaptation; Cognitive processes; Perceived autonomy; Pre-planning; Movement strategies; Attentional focus